Analisis Kemampuan Komunikasi Matematis Tertulis dalam Menyelesaikan Masalah Matematika Ditinjau dari Gaya Kognitif Siswa Kelas VIII SMP - Yolita Malaya; Nyoman Sridana; Hapipi Hapipi; Sudi Prayitno (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to analyze the written mathematical communication skills through the lence of cognitive style of the eighth-grade students of SMP Negeri 4 Praya Barat Daya in the academic year 2020/2021. With the subjects of research used is 4 students of class VIII A which is taken were in the form of GEFT test results . This study is a descriptive study. The instrument used is test GEFT and written mathematical communication skills test. The findings of the study showed that (a) Students with field-independent cognitivestyle depictedproper written mathematical communication skill. Students at this level were able to state ideas or mathematical solutions in their own language clearly and precisely, they also were able to state problems in the form of pictures, and were able to write down mathematical ideas and explanations correctly but were still not optimal. (b) Students with a field-dependent cognitive style had good mathematical communication ability. Students at this level were able to state ideas or mathematical solutions in their own language properlyyet are still incomplete, they were still not optimal in addressing problems in the form of images, and lastly, they werealso able to write mathematical ideas and explanations clearly and accurately.